Effect of a single dose of Saccharomyces cerevisiae var. boulardii on the occurrence of porcine neonatal diarrhoea - Hancox, L.R.; Le Bon, M.; Richards, P.J.; Guillou, D.; Dodd, Christine E.R.; Mellits, K.H. (Cambridge University Press, 2015)
Piglet neonatal diarrhoea is an important issue in modern pig production and is linked to increased mortality and poor growth rates, affecting long-term pig health, increasing use of medication and cost of production. Saccharomyces cerevisiae var. boulardii (SB) is a probiotic yeast with documented clinical efficacy in the prevention and treatment of diarrhoeal diseases in humans. The objectives of the current study were to evaluate the effect of SB on occurrence and severity of neonatal diarrhoea in piglets, mortality and growth rate. Forty-six litters (606 piglets) were randomly allocated to a control or SB treatment (n = 23 per treatment). Within 24 h of farrowing, piglets assigned to the SB treatment received a single oral dose of a paste containing 3.3×109CFU of SB CNCM I-1079. Piglets from the control litters received a placebo paste.# Piglet weight, mortality and diarrhoea were recorded up to day 7 of age. It was shown that numbers of diarrhoea days were significantly correlated with increased mortality rate and reduced weight gain ( P<0.05). SB treatment had no effect on growth or mortality in diarrhoeic litters. However, SB-supplemented litters had significantly lower faecal scores, indicating firmer faeces ( P<0.01) and fewer numbers of diarrhoeic days ( P<0.01) during the 1st week of life. Reduction in the number of diarrhoeic litters compared with the control group was observed following the probiotic administration ( P<0.05). These results highlight the detrimental effects of neonatal diarrhoea on pre-weaning performance and suggest that SB, by reducing diarrhoea duration and severity, has the potential of improving enteric health in the early stages of life in pigs.